Antimicrobial Activity of Amphiphilic Triazole-Linked Polymers Derived from Renewable Sources - Floros, Michael C.; Bortolatto, Janaína F. [UNESP]; Oliveira, Osmir B. [UNESP]; Salvador, Sergio L.; Narine, Suresh S. (American Chemical Society (ACS), 2016)
Conventional engineered polymers are strong, stable, and can interact desirably within the human body in implants and medical devices. However, bacterial colonization of medical devices and implants constructed from these materials results in numerous hospital acquired infections (HAI) and deaths each year. Polytriazole based plastics containing triazole rings and fatty acid derivatives have been synthesized from biological sources without catalysts or solvents. In this study, three amphiphilic polytriazoles with varying triazole density and hydrophilic/hydrophobic segments demonstrated broad spectrum, contact antimicrobial properties against both Gram positive and negative bacteria. SEM analysis of bacteria killed by these polymers evidence membrane damage, indicating that these polymers act by direct contact with bacterial membranes. Surface hydrophobicity of these polymers increased with increasing triazole group density, which also improved the antimicrobial efficacy. This work demonstrates that amphiphilic polytriazoles have antimicrobial properties and that future utilization of triazole modified polymers may produce self-sterilizing materials which resist bacterial contamination and formation of antibiotic resistant organisms, ideal characteristics for medically relevant biomaterials.
Keywords: amphiphilic; antimicrobial polymer; biomaterial; biomimetic; click chemistry; renewable